MODEL ACTIVE LEARNING SEBAGAI ALTERNATIF PENINGKATAN MUTU PEMBELAJARAN MAHASISWA PENERANGAN AGAMA HINDU - I Putu Suarnaya (Jurnal PASUPATI, 2020)
The purpose of this research is to provide an active learning and learning scenario based on Contextual Teaching and Learning to improve the quality of basic natural sciences students lighting and enhance the learning quality of basic natural sciences students with learning models of active learning based on Contextual Teaching and Learning. The design of this research is the study of action research class room with the subject of his research student amounted to 30 people. Data collection techniques with observations, interviews and end-of-cycle conducted test of learning results. For observation data and interviews are analyzed in a quantitative basis. While the test results are learned using performance indicators with graduation with a value of 7.5. Based on the results of analysis of actions that have been carried out, application of active learning based engagement model Contextual Teaching and Learning can improve the quality of learning basic natural Sciences in the description of 62.96% in cycle I To 85.19% in cycle II or an increase of 25.93%.